THE CONCEPT OF BILINGUALISM, TYPES AND CLASSIFICATION CRITERIA - Karimova Feruza Salimovna (Journals Park Publishing, 2024)
This article describes in detail the history of the emergence of bilingualism and the stages of its development. In humans, stages, preferences and difficulties in learning a second languages were reflected. Alternatively, information is also covered about the world and Uzbek researches who carried out research work on the phenomenon of bilingualism.
Keywords: Bilingualism, understanding, monolingualism, subject, linguistics, artificial, natural bilingualism, aspect, type, criterion, stage.